Between “Identity Politics” and “Politics of Influence”: The Role of Alternative Media in the Greek Protests in 2008 - Milioni, Dimitra L. (My University, 2012)
In December 2008 the killing of a teenager by a Greek policeman in central Athens set off the fiercest social unrest the country has witnessed in recent decades. For almost three weeks, thousands of angry youths articipated in mass demonstrations, in many cases resulting in rioting, looting and violent clashes with the police. Although new media technologies were heavily used by protesters, their role in the December 2008 vents has not been systematically studied. This paper explores how the “Greek Riots” in 2008 were reported in the alternative news network Indymedia Athens. A key question the study addresses is whether grassroots reporting in Indymedia Athens served activists’ need for communication and solidarity building (“politics of identity”) or functioned also as an “out-group” communication channel that could counter negative mainstream reporting and communicate protesters’ messages to a wider population (“politics of inclusion”). The findings how that during the first eight crucial days of the protests, the alternative outlet functioned first and foremost as a tool for coordination and creation of identity, through the exchange of mobilization information and direct action news. A frame analysis of thematic posts shows that compelling counterframes are created by rotesters’ narrations, but their potential to effectively challenge mainstream discourses and influence wider publics is unclear.
Keywords: Protest; Alternative media; Greece; Framing; Social movements